The contribution of CK2 and spleen tyrosine kinase (SYK) to CFTR trafficking and PKA-induced activity - Luz, Simão (2011)
Previously, the pleiotropic “master kinase” casein kinase 2 (CK2) was shown to interact with CFTR, the protein responsible for cystic fibrosis (CF). Moreover, CK2 inhibition abolished CFTR conductance in cell-attached membrane patches, native epithelial ducts, and Xenopus oocytes. CFTR possesses two CK2 phosphorylation sites (S422 and T1471), with unclear impact on its processing and trafficking. Here, we investigated the effects of mutating these CK2 sites on CFTR abundance, maturation, and degradation coupled to effects on ion channel activity and surface expression. We report that CK2 inhibition significantly decreased processing of wild-type (wt) CFTR, with no effect on F508del CFTR. Eliminating phosphorylation at S422 and T1471 revealed antagonistic roles in CFTR trafficking: S422 activation versus T1471 inhibition, as evidenced by a severe trafficking defect for the T1471D mutant. Notably, mutation of Y512, a consensus sequence for the spleen tyrosine kinase (SYK) possibly acting in a CK2 context adjacent to the common CF-causing defect F508del, had a strong effect on both maturation and CFTR currents, allowing the identification of this kinase as a novel regulator of CFTR. These results reinforce the importance of CK2 and the S422 and T1471 residues for regulation of CFTR and uncover a novel regulation of CFTR by SYK, a recognized controller of inflammation.